Medical management of inflammatory bowel disease among Canadian gastroenterologists - Jones, J (Pulsus Group Inc, 2011)
BACKGROUND: Little is known about physician perceptions of and practices in using infliximab – a biological agent that was approved in Canada for the treatment of Crohn’s disease in 2001, and for ulcerative colitis in 2006. OBJECTIVES: To describe Canadian gastroenterologists’ use and perceptions of infliximab in the treatment of refractory inflammatory bowel disease (IBD), and to identify factors that may influence a gastroenterologist’s decision to initiate infliximab therapy. METHODS: A postal questionnaire was distributed to all practicing clinicians captured in the 2007 membership of the Canadian Association of Gastroenterology. Each physician was contacted up to a maximum of three times. RESULTS: Of 466 questionnaires mailed out, responses were received from 336 (72%), with 292 respondents (63%) returning fully completed surveys. For 80% of respondents, IBD patients comprised less than 30% of their clinical practice. Most prescribed infliximab at an initial dose of 5 mg/kg (97%), prescribed loading doses at 0, 2 and 6 weeks (88%), premedicated with corticosteroids (74%), administered maintenance infusions at eight-week intervals (89%), co-administered immunosuppressive agents (81%) and continued infliximab ‘indefinitely’ as long as it was effective and well tolerated (76%). Most gastroenterologists (>70%) identified lack of drug insurance coverage and provincial funding criteria as important barriers to prescribing infliximab. CONCLUSIONS: Most Canadian gastroenterologists exhibited similar practice patterns with respect to the use of infliximab for induction and maintenance therapy of IBD. Common barriers to the initiation of infliximab therapy were identified.